The Influence of Technological Components of Work Upon Management Control - Bell, Gerald D. (Academy of Management Journal, 1965)
The article addresses the closeness of supervision and its impact on the predictability of subordinate's work demands and rule-usage. The author posits two theories: that the more unpredictable the work demand, the more distant the supervision and the more predictable the work demand, the closer the supervision. The article discusses closeness of supervision and rule-usage, relevant literature, research design, and the predictability of tasks as they relate to closeness of supervision and rule usage. The author notes the difficulty that technology creates in managing the work situation.